Passive Damping of Solar Array Vibrations Using Hyperelastic Shape Memory Alloy with Multilayered Viscous Lamina - Jae-Hyeon Park; Sung-Woo Park; Jong-Pil Kim; Hyun-Ung Oh (Aerospace, 2023)
A novel passive vibration-damping device is proposed and investigated for a large deployable solar array. One strategy for achieving high damping in a solar panel is using a yoke structure comprising a hyperelastic shape memory alloy and multiple viscous adhesive layers of acrylic tape. The effectiveness of the proposed system in achieving a high damping performance was demonstrated by conducting free vibration and low-level sine sweep tests using a solar array, and a 0.75-m-long flexible dummy structure was simulated. We also investigated the dependence of the damping performance of the proposed structure on the number of viscous lamina layers. Finally, the damping characteristics of the proposed system were assessed under predictable on-orbit temperature conditions.